Safety Talk and Check to Prevent Pesticide Toxicity among Farmer - Eka Lestari Mahyuni; Ida Yustina; Etty Sudaryati (Intelektual Pustaka Media Utama, 2017)
The problem at informal sector in particular for farmer when used the pesticides. In Sumber Mufakat village the farmers always use the pesticides without using the safety equipment and have direct contact with the pesticides exposure. The purpose of this research was to apply the safety talk and check method as prevention method to solve the pesticides toxicity that asses from safety and health of pesticide use behaviour. This preventive intervention research was using Participatory Action Research (PAR) design.The data collected by observation, quetionaire, and health check list. The population was all holticultura farmers in Sumber Mufakat village that divide in nine farmer's group. The sample collected by using proportional random sampling. The data will analyze by using qualitative descriptive. The result showed that the implication of safety talk and check method could prevent of pesticide exposure that present from safety and health of pesticides use behaviour. To support the action of safety talk method needed to develop one community that care about the farmers with government endorsement. The check method was very helpful the farmers to identify and predict their health. Both of it could be to cultivate the farmer in safety of pesticide used and early discovery of health symptom cause pesticide used.